Polishing pad, polishing device, article manufacturing method, and polishing pad manufacturing method

JP2025031464APending Publication Date: 2025-03-07CANON KK
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2024001513
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-08-24
Filing Date
2024-01-09
Publication Date
2025-03-07

AI Technical Summary

Benefits of technology

【0008】 本開示によれば、流体支持研磨に用いて流体圧を加えても流体が研磨面まで染み出さないため、高い追従性を維持することができる研磨パッドを提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025031464000001_ABST
    Figure 2025031464000001_ABST
Patent Text Reader

Abstract

To provide a polishing pad which can maintain high followability.SOLUTION: There is provided a polishing pad 10 in which a polishing layer 11 having a polishing surface 11S, and a sealing layer 13 having a support surface 13S are arranged in order, and the polishing surface 11S is provided on a surface, and the support surface 13S is provided on a rear face. A water contact angle of the support surface 13S is 90° or more. A water contact angle of the polishing surface 11S is smaller than the water contact angle of the support surface 13S. The polishing pad 10 is composed of a resin molding.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a polishing pad, a polishing apparatus, a method for manufacturing an article, and a method for manufacturing a polishing pad. [Background technology]

[0002] The polishing pad is attached to a base and is used in polishing processes performed in the finishing process of semiconductor substrates and optical lenses. In polishing, it is required to finish the entire surface uniformly to eliminate unevenness in the thickness of the workpiece to be processed. Semiconductor substrates and optical lenses come in a wide variety of sizes, from a few mm to a few m. In the case of large sizes, due to warping of the workpiece to be processed, a part of the polishing pad may contact unevenly, making it difficult to finish uniformly. Therefore, it is required to improve the conformability of the polishing pad to the shape of the workpiece, eliminate uneven contact, and finish uniformly. As a method that is effective in improving conformability, a laminated polishing pad described in Patent Document 1 and a fluid support polishing described in Patent Document 2 are known.

[0003] A laminated polishing pad is a pad that has layers with different hardness and elasticity in the thickness direction within a single pad. The upper layer is a hard layer with high hardness to hold the slurry on the polishing surface, and the lower layer is a soft layer with low hardness to follow the warp of the workpiece. The advantage of such a laminated polishing pad is that it does not require bonding with an adhesive, so there is no deterioration in followability due to unevenness in the thickness of the adhesive.

[0004] Fluid support polishing is a processing method in which the support surface of the polishing pad is supported by a fluid, and the fluid is filled at a constant pressure to match the warp of the workpiece, so it has high followability. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2003-220550 A [Patent Document 2] JP 2004-358591 A Summary of the Invention [Problem to be solved by the invention]

[0006] However, the water contact angle of the support surface of the conventional laminated polishing pad is large. When the laminated polishing pad is used for fluid support polishing, the fluid in the soft layer seeps out to the polishing surface, causing fluctuations in fluid pressure and making it impossible to maintain high compliance. In addition, when a sealing layer is attached to the laminated polishing pad with an adhesive, the unevenness in the thickness of the adhesive makes it impossible to maintain high compliance. [Means for solving the problem]

[0007] The polishing pad for solving the above problem comprises a polishing layer having a polishing surface and a sealing layer having a support surface, which are arranged in that order, the polishing surface being on the front side and the support surface being on the back side, the water contact angle of the support surface being 90° or more, the water contact angle of the polishing surface being smaller than the water contact angle of the support surface, and the polishing pad being made of a resin molded body. Effect of the Invention

[0008] According to the present disclosure, a polishing pad can be provided that can maintain high conformability even when used in fluid support polishing and fluid pressure is applied, since the fluid does not seep out to the polishing surface. [Brief description of the drawings]

[0009] [Figure 1] 1 is a schematic diagram of a polishing apparatus of the present disclosure. [Diagram 2] 2(a) and 2(c) are schematic diagrams of a polishing pad according to the present disclosure, in which (a) is a perspective view, and (b) and (c) are cross-sectional views taken along the line AA in FIG. [Diagram 3] 4A to 4C are diagrams showing a manufacturing flow of the polishing pad according to the present disclosure. [Figure 4] Schematic diagram illustrating a manufacturing process for the polishing pad of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] [Polishing equipment] 1 is a schematic diagram of a polishing apparatus according to the present disclosure. The polishing apparatus 1 includes a polishing pad 10, a base 5 for fixing the polishing pad 10, a fluid storage section 6 for storing a fluid that applies pressure from the lower surface side (sealing layer side) of the polishing pad 10, and a supply section 2 for supplying a slurry S such as water or a polishing liquid to the polishing surface of the polishing pad 10. The polishing apparatus 1 is a wet-type polishing apparatus, and is an apparatus of the type in which the polishing pad is supported by a fluid.

[0011] The fluid reservoir 6 has a function of storing a liquid or gas, which is a fluid applied to the support surface of the polishing pad 10 at a predetermined pressure. The type of fluid is not particularly limited, and gases include, for example, air, compressed air, and nitrogen. Liquids include, for example, pure water and polishing liquid. The magnitude of the pressure applied to the polishing pad 10 is not particularly limited as long as it is large enough to support the polishing pad 10, and is, for example, in the range of 3 kPa to 40 kPa. Preferably, it is in the range of 5 kPa to 20 kPa.

[0012] 1, a workpiece 3 to be processed is brought into contact with a polishing surface of a polishing pad 10 by a carrier workpiece 4 applying a force from above the workpiece 3. The workpiece 3 is, for example, a semiconductor substrate or an optical lens. In this specification, the workpiece 3 that has been polished is defined as an article.

[0013] [Polishing pad] 2 is a schematic diagram of a polishing pad according to the present disclosure, in which (a) is a perspective view, and (b) is an AA cross-sectional view taken along the line AA in the z-axis direction of (a) of FIG.

[0014] In Fig. 2, the plane horizontal to the polishing surface 11S is the xy plane, and the axis perpendicular to the xy plane is the z axis. The dashed line AA in Fig. 2(a) is parallel to the x axis and perpendicular to the y axis. In the polishing pad 10, the polishing layer 11, the intermediate layer 12, and the sealing layer 13 are arranged in this order from the polishing surface 11S toward the negative z direction. The polishing pad 10 of the present disclosure is a polishing pad in which the polishing layer and the sealing layer are arranged in this order, and has a polishing surface 11S on the front surface that is more hydrophilic than the support surface 13S, and a hydrophobic support surface on the back surface with a water contact angle of 90° or more.

[0015] The polishing layer 11 has a polishing surface 11S. The polishing surface 11S is the portion of the polishing pad 10 that comes into contact with the workpiece 3, and has a resin 7. The water contact angle of the polishing surface 11S is smaller than that of the support surface 13S. The polishing surface 11S has higher wettability than the support surface 13S, so the slurry S is more likely to wet and spread. When the slurry S is more likely to wet and spread on the polishing surface 11S, it is possible to reduce the surface roughness of the workpiece 3 compared to when the slurry S does not wet and spread sufficiently. The water contact angle of the polishing surface 11S is preferably less than 90°. The water contact angle of the polishing surface 11S is more preferably less than 75°, and even more preferably less than 25°.

[0016] It is preferable that air bubbles 8 are arranged on the polishing surface 11S. By arranging the air bubbles 8, the polishing surface 11S can store the slurry S on its surface. If the polishing surface 11S can store the slurry S, the slurry S can be supplied between the polishing pad 10 and the workpiece 3 during polishing even if the polishing pad 10 and the workpiece 3 are in contact with each other. The polishing layer 11 has a predetermined hardness, and thus has a function of suppressing the polishing pad 10 from following the undulating portion having a high spatial frequency, which is a portion of the workpiece 3 that is to be removed by polishing. The hardness of the polishing layer 11 can be set to a desired hardness by controlling the amount of the air bubbles 8 (average air bubble density). For example, the hollow portion of the hollow particles can be used as the air bubbles 8. If the content of the hollow particles is increased to increase the amount of the air bubbles 8, the hardness decreases, and if the content of the hollow particles is decreased to decrease the amount of the air bubbles 8, the hardness increases. The hardness is an indentation hardness, and is expressed in Pa. The average cell density of the polishing layer 11 is not particularly limited, but is, for example, in the range of 40% to 80%.

[0017] The polishing layer 11 preferably contains hydrophilic metal oxide particles 14 inside the resin 7. In this specification, "hydrophilic" means that the hydrophilicity rate is 0.50 or more, and "metal oxide particles having hydrophilicity" means that the hydrophilicity rate of the surface of the particle is 0.50 or more. The method for measuring the hydrophilicity rate will be described later. Since particles having hydrophilicity on the surface have a large surface free energy, when the polishing layer 11 contains the metal oxide particles 14, the polishing liquid or slurry is easily held by the polishing surface 11S. In other words, when the polishing layer 11 contains the hydrophilic metal oxide particles 14, the roughness of the polishing surface of the workpiece 3 is easily reduced. The type of metal oxide is not particularly limited, but silica and alumina are preferable from the viewpoint of large surface free energy. Silica and alumina may be used alone or together. If the content of the metal oxide particles 14 in the polishing layer 11 is less than 20%, the water contact angle becomes large, and there is a risk that sufficient polishing characteristics cannot be obtained. On the other hand, if the content exceeds 50 mass %, the hardness of the polishing layer 11 increases, and the conformability may become insufficient. Therefore, the content of the metal oxide particles 14 in the polishing layer 11 is preferably in the range of 20 mass % or more and 50 mass % or less.

[0018] The intermediate layer 12 is a portion disposed between the polishing layer 11 and the sealing layer 13, and contains the resin 7. In the polishing pad 10 of the present disclosure, the intermediate layer 12 may or may not be present. The intermediate layer 12 may contain air bubbles 8 or metal oxide particles 14 inside the resin 7, similar to the polishing layer 11. The intermediate layer 12 may contain air bubbles 8 or fluorine-based resin particles 9 inside the resin 7, similar to the sealing layer 13 described below. From the viewpoint of making it easier for the polishing pad 10 to follow the shape of the workpiece 3, it is preferable that the intermediate layer 12 has a lower hardness than the polishing layer 11. Therefore, it is preferable that the intermediate layer 12 has a lower average bubble density than the polishing layer 11.

[0019] The sealing layer 13 has a support surface 13S of the polishing pad 10. The support surface 13S is disposed on the surface of the polishing pad 10 opposite the polishing surface 11S. The support surface 13S is a portion to which fluid is applied from the fluid reservoir 6 at a predetermined pressure in fluid support polishing, and is a surface that is supported by the fluid during polishing operation. When supported by liquid, the support surface 13S also has the function of preventing water from entering the polishing surface 11S.

[0020] The water contact angle of the support surface 13S is 90° or more. Since the water contact angle of the support surface 13S is larger than that of the polishing surface 11S, the polishing pad 10 has a structure in which liquid, which is a fluid, is less likely to penetrate. In other words, the support surface 13S is more hydrophobic than the polishing surface 11S. A preferred water contact angle of the support surface 13S is in the range of 90° or more and 150° or less. In order to increase the water contact angle to more than 150°, it is necessary to include a large amount of fluorine-based resin particles 9, which will be described later, and as a result, there is a risk of the hardness becoming high.

[0021] The sealing layer 13 has a resin 7 and bubbles 8. The average bubble density of the sealing layer 13 is not particularly limited, but is, for example, in the range of 40% to 80%. If the average bubble density of the sealing layer 13 is too high, the bubbles tend to be connected together. In that case, the fluid provided from the fluid storage section 6 may reach the workpiece 3 through the support surface 13S, the sealing layer 13, the intermediate layer 12, the polishing layer 11, and the polishing surface 11S. In addition, the thickness of the sealing layer 13 (the length in the z direction in FIG. 2(b)) is preferably thinner than the thickness of the polishing layer 11 and the thickness of the intermediate layer 12.

[0022] From the viewpoint of increasing the hydrophobicity of the sealing layer 13, the sealing layer 13 preferably contains fluorine-based resin particles 9. The type of fluorine-based resin particles used may be at least one selected from the group consisting of polytetrafluoroethylene (PTFE = tetrafluoroethylene resin), tetrafluoroethylene-perfluoroalkoxyethylene copolymer resin (PFA), tetrafluoroethylene-hexafluoropropylene copolymer resin (FEP), tetrafluoroethylene-hexafluoropropylene-perfluoroalkoxyethylene copolymer resin (EPE), tetrafluoroethylene-ethylene copolymer resin (ETFE), trifluorochloroethylene copolymer resin (PCTFE), trifluorochloroethylene-ethylene copolymer resin (ECTFE), vinylidene fluoride resin (PVDF), and polyvinyl fluoride resin (PVE). Among these, polytetrafluoroethylene (PTFE) is preferred. PTFE is a substance with excellent heat resistance and chemical resistance and a small surface free energy of 18.5 mN / m, which has the effect of increasing the hydrophobicity of the sealing layer 13 and enhancing the function of preventing water from entering the polishing surface 11S. The content of the fluororesin particles 9 in the sealing layer 13 is preferably in the range of 20% by mass to 50% by mass. The content of the fluororesin particles 9 provides a good balance between the water contact angle and hardness, and sufficient conformability can be obtained.

[0023] As shown in FIG. 2(c), the bubbles 8 preferably have a flat shape crushed in the stacking direction. This is because high conformability can be maintained even with respect to the shape and warping of the workpiece 3. In particular, the bubbles 8 preferably have a flat shape crushed in the stacking direction in all layers. In the polishing pad 10 of the present disclosure, the diameter of the bubbles varies from large to small, and it is preferable that the diameter of the largest bubble exceeds the thickness of the layer. If the bubbles 8 do not have a flat shape crushed in the stacking direction, the bubbles in all layers tend to be connected. In that case, there is a risk that the fluid provided from the fluid storage section 6 will reach the workpiece 3 through the support surface 13S, the sealing layer 13, the intermediate layer 12, the polishing layer 11, and the polishing surface 11S. Therefore, it is preferable that the thickness of the flat shape is equal to or less than the thickness of the layer in all layers. The diameter (average bubble diameter) of the bubbles in the polishing surface 11S is preferably in the range of 50 μm to 300 μm. If the thickness is less than 50 μm, depending on the manufacturing conditions, it may not be possible to store the slurry, and an insufficient amount of the slurry S may be supplied to the polishing pad 10 and the workpiece 3. If the thickness is more than 300 μm, uneven pressure may be applied to the surface of the workpiece 3, resulting in increased surface roughness.

[0024] The polishing pad 10 is a resin molded body. That is, the polishing surface 11S, the polishing layer 11, the intermediate layer 12, the sealing layer 13, and the support surface 13S are molded integrally without the use of adhesive. The resin molded body is preferably a foamed body. In this case, the polishing surface 11S has an uneven shape. The raw material of the resin material which is the cured product constituting the resin molded body is not particularly limited, and for example, polyurethane, polyethylene, polypropylene, polystyrene, polyester, nylon, polyvinyl chloride, polyvinylidene chloride, polybutene, polyacetal, polyphenylene oxide, polyvinyl alcohol, polymethyl methacrylate, polysulfone, polyethersulfone, polyetherketone, polyetheretherketone, polyamideimide, polycarbonate, polyarylate, liquid crystal polymer, aromatic polysulfone resin, biodegradable polyester resin, polyamide resin, polyimide resin, fluororesin, ethylene-propylene resin, ethylene-ethyl acrylate resin, epoxy resin, acrylic resin, norbornene resin, styrene copolymer (for example, vinyl polyisoprene-styrene copolymer, butadiene-styrene copolymer, acrylonitrile-styrene copolymer, acrylonitrile-butadiene-styrene copolymer, etc.), natural rubber, synthetic rubber, and thermoplastic elastomer can be used. These exemplified resin materials may be used alone, or may be mixed or copolymerized. From the viewpoint of excellent abrasion resistance and facilitating the manufacturing process described later, it is preferable that polyurethane is the main component. In the present disclosure, the main component of a resin molded body refers to the component that contains the heaviest mass of the resin material when the resin molded body is composed of multiple resin materials. The proportion of polyurethane in the resin molded body is 50 mass% or more, preferably 70 mass% or more, and more preferably 90 mass% or more. The manufacturing method of the resin molded body will be described later.

[0025] The water vapor permeability of the polishing pad 10 is 25 g / m 2It is preferable that the water vapor permeability is 1.4 g / m or less. If the water vapor permeability is below this value, even if fluid is applied from the fluid storage section 6 to the support surface 13S of the polishing pad 10, the fluid is less likely to leak onto the polishing surface 11S, and the polishing pad 10 is more likely to conform to the shape of the workpiece 3. On the other hand, if the water vapor permeability is greater than this value, there is a risk that the fluid will leak into the polishing layer 11, and if the fluid leaks, it will be difficult for the polishing pad 10 to conform to the shape of the workpiece 3. If it becomes difficult for the polishing pad 10 to conform to the shape of the workpiece 3, there is a risk that the polishing process will not progress sufficiently and the surface roughness of the workpiece 3 will not be sufficiently reduced. A more preferable water vapor permeability is 13 g / m 2 Less than 24 hours.

[0026] The thickness of the polishing pad (length in the z direction in FIG. 2(b)) is preferably in the range of 0.3 mm to 2.0 mm. This is because a thickness in this range allows the polishing pad 10 to easily conform to the warpage and shape of the workpiece 3. The polishing layer 11 becomes thinner due to wear on the pad surface caused by the polishing process, so from a cost perspective, it is preferably 1.0 mm or more. Furthermore, the thinner the sealing layer 13, the wider the area that can be used for polishing, so it is preferably 0.5 mm or less.

[0027] As described above, the polishing pad of the present disclosure is made of a resin molded body in which a polishing layer having a polishing surface with a water contact angle smaller than that of the support surface and a sealing layer having a support surface with a water contact angle of 90° or more are laminated in this order, so that even if fluid pressure is applied when used for fluid-supported polishing, the fluid does not seep out to the polishing surface. In addition, since it is made of a resin molded body without an adhesive layer made of an adhesive, it can maintain high conformability to the shape and warping of the workpiece 3. Therefore, the polishing pad of the present disclosure can sufficiently reduce the surface roughness of the workpiece compared to conventional polishing pads for fluid-supported polishing.

[0028] [Polishing pad manufacturing method] Next, a method for manufacturing the polishing pad will be described. Although the method for manufacturing the polishing pad 10 of the present disclosure is not particularly limited, a preferred embodiment will be described with reference to FIGS.

[0029] First, the sealing layer precursor is placed in a mold and then heated to be provisionally cured (S1, FIG. 4(a)). The sealing layer precursor 13A is a mixture containing a thermoplastic resin, a curing agent, and the first hollow particles. The sealing layer precursor 13A becomes the sealing layer 13 of the polishing pad 10 after the main curing. The surface of the sealing layer 13 becomes the support surface 13S. The size and type of the mold 20 are not particularly limited, and the mold can be made to a desired size according to the shape of the polishing pad 10 to be manufactured. The mold 20 is, for example, a metal mold. In addition, it is preferable that the upper surface or the opposing side of the mold is movable and has an openable and closable vent hole for discharging excess resin when the mold is closed. In addition, it is preferable to remove air bubbles using a defoamer or the like when mixing the thermoplastic resin, the curing agent, and the first hollow particles. The temperature of the provisional curing may be equal to or lower than the temperature of the main curing described later, and can be appropriately set depending on the material of the thermoplastic resin used. In addition, when the temperature of the provisional curing and the temperature of the main curing are the same, it is preferable that the time of the provisional curing is shorter than the time of the main curing.

[0030] Next, the intermediate layer precursor is placed on the sealing layer precursor 13A provisionally cured in the mold, and then heated to provisionally cure (S2, FIG. 4(b)). The intermediate layer precursor 12A is a mixture containing a thermoplastic resin, a curing agent, and third hollow particles. The intermediate layer precursor 12A becomes the intermediate layer 12 of the polishing pad 10 after full curing. In addition, when mixing the thermoplastic resin, the curing agent, and the third hollow particles, it is preferable to remove air bubbles using a defoamer or the like. The temperature of the provisional curing may be equal to or lower than the temperature of full curing described later, and can be appropriately set depending on the material of the thermoplastic resin used. When the hardness of the intermediate layer 12 is greater than the hardness of the sealing layer 13, the content and / or particle size of the third hollow particles are selected so that the bubble density of the third hollow particles is smaller than that of the sealing layer 13. In that case, the average particle size of the third hollow particles is preferably smaller than the average particle size of the first hollow particles. In addition, the linear expansion coefficient of the third hollow particles is preferably smaller than the linear expansion coefficient of the first hollow particles. When the hardness of intermediate layer 12 is lower than that of sealing layer 13, the content and / or particle size of the third hollow particles are selected so that the bubble density is higher than that of sealing layer 13. In this case, the average particle size of the third hollow particles is preferably larger than the average particle size of the first hollow particles. In addition, the linear expansion coefficient of the third hollow particles is preferably larger than the linear expansion coefficient of the first hollow particles.

[0031] Next, the polishing layer precursor is placed on top of the intermediate layer precursor that has been provisionally cured in the mold, and then heated to provisionally cure (S3, FIG. 4(c)). The polishing layer precursor 11A is a mixture containing a thermoplastic resin, a curing agent, and second hollow particles. After being fully cured, the polishing layer precursor 11A becomes the polishing layer 11 of the polishing pad 10. When mixing the thermoplastic resin, the curing agent, and the second hollow particles, it is preferable to remove air bubbles using a defoamer or the like. The provisional curing temperature may be equal to or lower than the fully curing temperature described below, and can be appropriately set depending on the thermoplastic resin material used. When the provisional curing temperature and the fully curing temperature are the same, it is preferable that the provisional curing time is shorter than the fully curing time.

[0032] Then, the sealing layer precursor, the intermediate layer precursor, and the polishing layer precursor are heated to be fully cured while compressing the inside of the mold and holding until they no longer flow (S4, FIG. 4(d)). By fully curing the sealing layer precursor, the intermediate layer precursor, and the polishing layer precursor, the sealing layer, the intermediate layer, and the polishing layer are formed, and a resin foam containing flat bubbles can be produced by compression in the mold. The temperature for fully curing may be equal to or higher than the temperature for provisional curing described above, and can be appropriately set depending on the thermoplastic resin material used. When the temperature for provisional curing and the temperature for fully curing are the same, it is preferable that the time for fully curing is longer than the time for provisional curing. For compression in the mold, a top cover is placed on the top surface of the mold, and the top cover is moved while curing in the fully curing process, and this state is held until it no longer flows. Since the provisionally cured resin retains its fluidity under high temperature and high pressure, it is possible to flatten the bubble shape by utilizing this. The degree of compression is preferably 50 to 95% of the original thickness, more preferably 55 to 75%. In this case, the bubbles become flat in the direction of movement of the mold top cover. In addition, when flat bubbles are not to be formed, the partially cured precursor of the polishing pad may be released from the mold 20 after the step S3, and then the fully cured precursor may be performed.

[0033] By the above steps, the polishing pad 10 of the present disclosure can be manufactured.

[0034] As described above, the manufacturing method of the polishing pad according to the present disclosure does not include a step of using an adhesive, and therefore can provide a polishing pad that can maintain high conformability to the shape and warping of the workpiece 3. Therefore, according to the manufacturing method of the polishing pad according to the present disclosure, it is possible to provide a polishing pad that can sufficiently reduce the surface roughness of the workpiece, compared to conventional polishing pads for fluid support polishing.

[0035] In the above-mentioned manufacturing method, the seal layer precursor, the intermediate layer precursor, and the polishing layer precursor are put into a mold in this order, and then provisional curing and final curing are carried out, but the polishing layer precursor, the intermediate layer precursor, and the seal layer precursor can also be put into a mold in this order, and then provisional curing and final curing are carried out.In addition, in the above-mentioned manufacturing method, the hardness of each layer is adjusted by the size or content of hollow particles, but this is not limited to this embodiment.For example, the precursor of each layer can be intentionally foamed when mixed to control each hardness.

[0036] Also, step S2 may be omitted when manufacturing a polishing pad 10 that does not have an intermediate layer 12. In that case, the polishing layer precursor is placed directly on the provisionally cured sealing layer precursor. EXAMPLES

[0037] The present disclosure will be described more specifically below with reference to examples, but the present disclosure is not limited to the following examples.

[0038] Prior to the description of the Production Examples, the evaluation methods of the Examples and Comparative Examples will be described.

[0039] [Polishing pad evaluation method] (water contact angle) Measuring instrument: Contact angle meter (AST Products.inc: VCA-2500XE) Test method: Pure water (1 μL) was dropped onto the polishing surface and supporting surface of the polishing pad from a microsyringe coated with PTFE (polytetrafluoroethylene) with an inner diameter of 0.1 mm, and the water contact angle was measured immediately thereafter.

[0040] (Hydrophilicity rate) Measuring instrument: Fourier transform infrared spectrometer (PerkinElmer: FT-IR-NIRA) Test method: Silica particles have a surface IR spectrum of 7300 cm, which represents Si-OH. -1 The absorbance at 4500 cm represents SiO2. -1 The alumina particles have an absorbance of 3690 cm, which represents Al-OH in the IR spectrum of their surface.-1 The absorbance at 7425 cm -1 The absorbance was calculated by dividing the absorbance at

[0041] (Water vapor permeability) Measuring device: Gas permeability test device (Mocon.inc: PERMATRAN-W 1 / 50) Test method: Evaluation was performed according to JIS Z 0208: Moisture permeability test method (cup method) (test conditions: temperature 40°C, humidity 90% RH).

[0042] (Average bubble density) Measuring instrument: Color 3D laser microscope (Keyence: VK-9700) Test method: The cross section of the test piece (10 mm x 10 mm) was measured using a 10x objective lens, and then the resin and bubble areas were converted to grayscale using image processing and binarized at 125 gradations to calculate the average bubble density.

[0043] (average bubble diameter) Measuring instrument: Color 3D laser microscope (Keyence: VK-9700) Test method: The entire polished surface of the test piece (10 mm x 10 mm) was stitch-measured using a 10x objective lens, and then the resin and bubble parts were converted to grayscale using image processing. The bubble diameters were then tallied from the image binarized at 125 gradations, and the average bubble diameter was calculated.

[0044] (bubble thickness) Measuring instrument: Color 3D laser microscope (Keyence: VK-9700) Test method: The cross section of the test piece (10 mm x 10 mm) was measured using a 10x objective lens, and then the resin and bubble parts were converted to grayscale using image processing, and the thickness of the bubbles in the layering direction was measured from the binarized image at 125 gradations.

[0045] (Thickness of each layer) Measuring instrument: Color 3D laser microscope (Keyence: VK-9700) Test method: The cross section of the test piece (10 mm x 10 mm) was similarly measured with a 10x objective lens to measure the thickness of each layer.

[0046] (Workpiece roughness) Measuring instrument: White light interferometer (Zygo: CP300) Test method: A 5x objective lens was used to measure the stitching of a test workpiece (φ80mm) from a point moved 35mm to the left of the center to a point moved 35mm to the right of the center, and the Rz (JIS B 0601-2001) of the entire measured area was evaluated. The resolution was 0.01nm.

[0047] (Following ability) Test method: A workpiece made of a φ80mm glass substrate with a surface roughness of 50nmRz was polished for 30 minutes while adding cerium oxide (K30-9, manufactured by Mireiku Co., Ltd.) as a slurry, and the maximum roughness Rz was evaluated. At this time, the judgment value for whether the polishing pad was able to follow the workpiece was set to a maximum roughness of 1nmRz. This is because if the polishing pad does not follow the workpiece and is not able to polish it uniformly, unprocessed areas will remain and the roughness will not be below this judgment value. If the roughness is below 1nmRz, it is rated A, and if it is greater than 1nmRz, it is rated B.

[0048] (Components) Measuring instrument: FE-SEM (Product name: JSM-IT500HR / LA, manufactured by JEOL Ltd.) Test method: A method for measuring the content of metal oxide particles will be described. In a cross section in the thickness direction when the polishing layer is cut parallel to the longitudinal direction, a square with a side length of 1 mm (stitched image size of 260 um x 190 um) was arbitrarily selected and set as a first observation area between the polishing surface and a position at a depth of 5 μm. An EDS image was obtained in the first observation area under conditions of 500 times magnification and 10 kV, and a binary processing was performed using a numerical calculation software (product name: MATLAB (registered trademark), manufactured by Math Work Co., Ltd.) to obtain a binary image. Then, in the obtained binary image, the ratio of the number of pixels in the area corresponding to hydrophilic metal oxide particles to the number of pixels in the entire measurement area (resolution is 2083 vertical x 2083 horizontal) was calculated.

[0049] The method for measuring the content of fluororesin particles will be described. In the cross section of the thickness direction when the sealing layer is cut parallel to the longitudinal direction, a square with a side length of 50 μm (image size 260 um × 190 um stitched) was arbitrarily selected and set as a second observation area between the support surface and a position at a depth of 5 μm. In the second observation area, an EDS image was acquired under conditions of 500 times magnification and 10 kV, and a binary processing was performed using a numerical calculation software (product name: MATLAB, manufactured by Math Work) to obtain a binary image. Then, in the obtained binary image, the ratio of the number of pixels in the area corresponding to the fluororesin particles to the number of pixels in the entire measurement area (resolution is 2083 vertical × 2083 horizontal) was calculated.

[0050] [Polishing pad manufacturing] Example 1 As the resin material for the sealing layer, 28.98 g of thermoplastic resin diphenylmethane diisocyanate (MDI) type polyurethane elastomer, Coronate 4370 (manufactured by Tosoh Corporation), was weighed out, and 20.28 g of polyol-based curing agent, Nipporan 4479 (manufactured by Tosoh Corporation), was weighed out and mixed. As the first hollow particles, 0.78 g of Matsumoto Microsphere FN-78D (manufactured by Matsumoto Yushi Seiyaku Co., Ltd.) and 3.06 g of polytetrafluoroethylene particles, ALGOFLON L203R (manufactured by Solvey Co., Ltd.), were weighed out, and mixed into this mixture. The mixture was mixed for 3 sets (48 seconds in total), with 16 seconds being the least affected by heat, using an automixer (2-913-01 Automixer AS100, manufactured by AS ONE Corporation, rotation speed 3000 rpm), and the sealing layer precursor was prepared.

[0051] Similarly, 28.98 g of diphenylmethane diisocyanate (MDI) type polyurethane elastomer, Coronate 4370 (manufactured by Tosoh Corporation), which is a thermoplastic resin, was weighed out as the resin material for the polishing layer, and 20.28 g of polyol-based hardener, Nipporan 4479 (manufactured by Tosoh Corporation) was weighed out and mixed as the hardener. 0.99 g of Matsumoto Microsphere F-80DE (manufactured by Matsumoto Yushi Seiyaku Co., Ltd.) was weighed out as the third hollow particle into this mixture, and the mixture was mixed for 3 sets (48 seconds in total) of 16 seconds, which is the least affected by heat, using an automixer (2-913-01 Automixer AS100, manufactured by AS ONE Corporation, rotation speed 3000 rpm) to prepare the polishing layer precursor. □ 2.67g of sealing layer precursor is put into a square mold with a bottom surface of 200×200mm, and it is temporarily cured in an electric furnace at 120°C for 10 minutes. Next, 8.00g of polishing layer precursor is put on the temporarily cured sealing layer precursor, and it is primarily cured in an electric furnace at 120°C for 1 hour. After that, the temporarily cured polishing pad precursor is released from the mold. Then, the polishing pad precursor is secondary cured under the condition of 120°C for 8 hours, and the polishing pad of Example 1 is obtained. The polishing pad of Example 1 had a thickness of 0.11 mm for the sealing layer and 0.21 mm for the polishing layer. The water contact angle of the support surface was 90.6°, and the bubble density of the sealing layer was 62%. The water contact angle of the polishing surface was 73.9°, and the bubble density of the polishing layer was 61%. The water vapor permeability was 18.6 g / m 2 -It was 24 hours. The evaluation results of the water contact angle of the polishing surface, the water contact angle of the support surface, the fluororesin content, the water vapor permeability, the roughness of the workpiece, and the conformability are summarized in Table 1. From Table 1, it was confirmed that in Example 1, the roughness was 1 nmRz or less, so that the polishing pad could conform sufficiently to the workpiece.

[0052] Example 2 In Example 2, the amount of polytetrafluoroethylene particles was increased to 7.5g in order to increase the water contact angle of the sealing layer. The procedure from degassing to curing was the same as in Example 1 to prepare the polishing pad of Example 2. 16.8g of the sealing layer precursor was placed in a mold, and 42.8g of the polishing layer precursor was placed on the provisionally cured sealing layer precursor, followed by full curing.

[0053] The polishing pad of Example 2 had a thickness of 0.63 mm for the sealing layer and 1.07 mm for the polishing layer. The water contact angle of the support surface was 149.5°, and the bubble density of the sealing layer was 59%. The water contact angle of the polishing surface was 74.7°, and the bubble density of the polishing layer was 62%. The water vapor permeability was 12.1 g / m 2 -It was 24 hours.

[0054] From Table 1, it was confirmed that the polishing pad could sufficiently follow the workpiece because the roughness was 1.0 nmRz or less in Example 2. In addition, it was confirmed that the water contact angle of the sealing layer was larger than that of Example 1, but the effect on the maximum roughness was small.

[0055] Example 3 The precursor was prepared in the same manner as in Example 2, but in Example 3, 0.47 g of hydrophilic silica AEROXIDE (registered trademark) 380PE (manufactured by Nippon Aerosil Co., Ltd.) with a hydrophilicity rate of 0.51 was added to the polishing layer precursor. The procedure from degassing to curing was the same as in Example 1 to prepare the polishing pad of Example 3. 12.53 g of the sealing layer precursor was placed in a mold and temporarily cured, after which 38.00 g of the polishing layer precursor was placed on the sealing layer precursor and fully cured.

[0056] The polishing pad of Example 3 had a thickness of 0.47 mm for the sealing layer and 0.95 mm for the polishing layer. The water contact angle of the support surface was 120.8°, and the bubble density of the sealing layer was 59%. The water contact angle of the polishing surface was 49.5°, and the bubble density of the polishing layer was 60%. The water vapor permeability was 15.3 g / m 2 -It was 24 hours.

[0057] From Table 1, it was confirmed that the roughness of Example 3 was 1.0 nmRz or less, and therefore the polishing pad was able to sufficiently follow the workpiece. In addition, compared to Example 2, it is believed that the inclusion of hydrophilic metal oxide particles made it easier for the polishing liquid to be retained on the polishing surface, resulting in a lower roughness.

[0058] Example 4 The precursor was prepared in the same manner as in Example 3, but in Example 4, 0.24 g of hydrophilic alumina AEROXIDE (registered trademark) Alu130 (manufactured by Nippon Aerosil Co., Ltd.) with a hydrophilicity rate of 0.52 was added to the polishing layer precursor. The procedure from degassing to curing was the same as in Example 1 to prepare the polishing pad of Example 4. 12.53 g of the sealing layer precursor was placed in a mold and temporarily cured, after which 38.00 g of the polishing layer precursor was placed on the sealing layer precursor and fully cured.

[0059] The polishing pad of Example 4 had a thickness of 0.47 mm for the sealing layer and 0.95 mm for the polishing layer. The water contact angle of the support surface was 121.9°, and the bubble density of the sealing layer was 59%. The water contact angle of the polishing surface was 49.8°, and the bubble density of the polishing layer was 60%. The water vapor permeability was 15.3 g / m 2 -It was 24 hours.

[0060] From Table 1, it was confirmed that the polishing pad could sufficiently follow the workpiece because the roughness was 1.0 nmRz or less in Example 4. In addition, compared with Example 3, it was confirmed that it is possible to obtain polishing accuracy equivalent to that of hydrophilic silica even with hydrophilic alumina.

[0061] Example 5 The precursor was prepared in the same manner as in Example 3, but in Example 5, 1.15 g of hydrophilic silica AEROXIDE (registered trademark) 380PE (manufactured by Nippon Aerosil Co., Ltd.) with a hydrophilicity rate of 0.51 was added to the polishing layer precursor. The procedure from degassing to curing was the same as in Example 1 to prepare the polishing pad of Example 5. 12.53 g of the sealing layer precursor was placed in a mold and temporarily cured, after which 43.60 g of the polishing layer precursor was placed on the sealing layer precursor and fully cured.

[0062] The polishing pad of Example 5 had a thickness of 0.47 mm for the sealing layer and 1.09 mm for the polishing layer. The water contact angle of the support surface was 120.8°, and the bubble density of the sealing layer was 60%. The water contact angle of the polishing surface was 49.5°, and the bubble density of the polishing layer was 62%. The water vapor permeability was 14.8 g / m 2 -It was 24 hours.

[0063] From Table 1, it was confirmed that the roughness of Example 5 was 1.0 nmRz or less, and therefore the polishing pad was able to sufficiently follow the workpiece. In addition, compared to Example 2, it is believed that the inclusion of hydrophilic metal oxide particles made it easier for the polishing liquid to be retained on the polishing surface, resulting in a lower roughness.

[0064] Example 6 The precursor was prepared in the same manner as in Example 5, but in Example 6, Matsumoto Microsphere FN-78D (manufactured by Matsumoto Yushi Seiyaku Co., Ltd.) was added to the polishing layer precursor as the third hollow particle. In addition, the amount of precursor was increased to 66.06g of the polishing layer precursor on top of the sealing layer precursor after putting 18.98g of the sealing layer precursor into the mold for compression and temporarily curing it. After that, the φ3mm vent hole provided on the side of the mold was opened, and the top cover was placed on the top of the mold. While heating and fully curing, the top cover was moved to compress the thickness to 66% of the thickness before compression, and the state was maintained until the resin stopped flowing. In addition, excess resin was discharged from the vent hole.

[0065] The polishing pad of Example 6 had a thickness of 0.47 mm for the sealing layer and 1.09 mm for the polishing layer. The thickness of the bubbles in the lamination direction was a maximum of 0.42 mm for the sealing layer and 0.98 mm for the polishing layer, and the average bubble diameter on the polishing surface was 300 μm. The maximum bubble diameter was 1.8 mm, and the bubbles were flattened in the lamination direction. The water contact angle on the support surface was 120.6°, and the bubble density of the sealing layer was 60%. The water contact angle on the polishing surface was 49.5°, and the bubble density of the polishing layer was 62%. The water vapor permeability was 9.2 g / m 2 -It was 24 hours.

[0066] From Table 1, it was confirmed that the polishing pad was able to sufficiently follow the workpiece in Example 6 because the roughness was 1.0 nmRz or less. In addition, compared to Example 5, it is considered that the roughness was reduced due to the improved followability caused by making the bubbles flat, which prevented the bubbles in each layer from connecting.

[0067] Example 7 The precursor was prepared in the same manner as in Example 5, but in Example 7, Matsumoto Microsphere FN-78D (manufactured by Matsumoto Yushi Seiyaku Co., Ltd.) was added to the polishing layer precursor as the third hollow particle. In addition, the amount of precursor was increased to 87.20 g of the polishing layer precursor after putting 25.06 g of the sealing layer precursor into the mold for compression and temporarily curing it, on top of the sealing layer precursor. Then, the φ3 mm vent hole provided on the side of the mold was opened, and the top cover was placed on the top of the mold. While heating and fully curing, the top cover was moved to compress the thickness to 50% of the thickness before compression, and the state was maintained until the resin stopped flowing. In addition, excess resin was discharged from the vent hole.

[0068] The polishing pad of Example 7 had a thickness of 0.47 mm for the sealing layer and 1.09 mm for the polishing layer. The thickness of the bubbles in the lamination direction was a maximum of 0.30 mm for the sealing layer and 0.74 mm for the polishing layer, and the average bubble diameter on the polishing surface was 300 μm. The maximum bubble diameter was 2.1 mm, and the bubbles were flattened in the lamination direction. The water contact angle on the support surface was 120.6°, and the bubble density of the sealing layer was 60%. The water contact angle on the polishing surface was 49.5°, and the bubble density of the polishing layer was 62%. The water vapor permeability was 8.4 g / m 2 -It was 24 hours.

[0069] From Table 1, it was confirmed that the polishing pad could sufficiently follow the workpiece in Example 7 because the roughness was 1.0 nmRz or less. In addition, compared to Example 6, it was confirmed that the thickness of the bubbles was thin, but the effect on the maximum roughness was small.

[0070] Example 8 The precursor was prepared in the same manner as in Example 5, but in Example 6, Matsumoto Microsphere F-65DE (manufactured by Matsumoto Yushi Seiyaku Co., Ltd.) was added to the polishing layer precursor as the third hollow particle. In addition, the amount of precursor was increased to 66.06g of the polishing layer precursor on top of the sealing layer precursor after putting 18.98g of the sealing layer precursor into the mold for compression and temporarily curing it. After that, the φ3mm vent hole provided on the side of the mold was opened, and the top cover was placed on the top of the mold. While heating and fully curing, the top cover was moved to compress the thickness to 66% of the thickness before compression, and the state was maintained until the resin stopped flowing. In addition, excess resin was discharged from the vent hole.

[0071] The polishing pad of Example 5 had a thickness of 0.47 mm for the sealing layer and 1.09 mm for the polishing layer. The thickness of the bubbles in the lamination direction was a maximum of 0.42 mm for the sealing layer and 0.98 mm for the polishing layer, and the average bubble diameter on the polishing surface was 50 μm. The maximum bubble diameter was 1.8 mm, and the bubbles were flattened in the lamination direction. The water contact angle on the support surface was 120.6°, and the bubble density of the sealing layer was 60%. The water contact angle on the polishing surface was 49.5°, and the bubble density of the polishing layer was 62%. The water vapor permeability was 9.2 g / m 2 -It was 24 hours.

[0072] From Table 1, it was confirmed that the polishing pad could sufficiently follow the workpiece because the roughness was 1.0 nmRz or less in Example 5. In addition, compared with Example 6, it was confirmed that the average bubble diameter was smaller, but the effect on the maximum roughness was small.

[0073] Example 9 In Example 9, the amount of polytetrafluoroethylene particles was increased to 8.15 g in order to increase the water contact angle of the sealing layer. The procedure from degassing to curing was the same as in Example 1 to prepare the polishing pad of Example 6.

[0074] The polishing pad of Example 9 had a thickness of 0.51 mm for the sealing layer and 0.86 mm for the polishing layer. The water contact angle of the support surface was 150.6°, and the bubble density of the sealing layer was 59%. The water contact angle of the polishing surface was 71.8°, and the bubble density of the polishing layer was 60%. The water vapor permeability was 9.2 g / m 2 -It was 24 hours.

[0075] From Table 1, it was confirmed that the polishing pad could sufficiently follow the workpiece in Example 9 because the roughness was 1.0 nmRz or less. In addition, it was confirmed that the water contact angle of the sealing layer was larger than that of Example 1, but the effect on the maximum roughness was small.

[0076] Comparative Example 1 The precursor was prepared in the same manner as in Example 3. Then, 12.53 g of the sealing layer precursor was put into a mold and cured in a furnace at 120°C for 4 hours. The cured sealing layer precursor was then released from the mold. Next, 43.60 g of the polishing layer precursor was put into the mold and cured for 4 hours at 120°C, and then released from the mold. Then, the sealing layer precursor and the polishing layer precursor were bonded with 1.1 g of adhesive (Cemedine Super X) to prepare the polishing pad of Comparative Example 1.

[0077] The polishing pad of Comparative Example 1 had a sealing layer thickness of 0.47 mm, a polishing layer thickness of 0.95 mm, and an adhesive thickness of 0.09 mm. The water contact angle of the support surface was 120.8°, and the bubble density of the sealing layer was 60%. The water contact angle of the polishing surface was 15.1°, and the bubble density of the polishing layer was 62%. The water vapor permeability was 15.1 g / m 2 -It was 24 hours.

[0078] The roughness was evaluated in the same manner as in Example 1. From Table 1, the roughness in Comparative Example 1 was greater than 1.0 nmRz. This was because gaps occurred during attachment, causing uneven adhesion. It is believed that air or polishing liquid entered the gaps, causing a distribution in the liquid pressure, which deteriorated the ability of the polishing pad to follow the shape of the workpiece to be polished, making it impossible to obtain high surface accuracy.

[0079] Comparative Example 2 The polishing pad was prepared in the same manner as in Example 1. At this time, polytetrafluoroethylene particles were not added to the sealing layer precursor. The subsequent procedures from degassing to curing were the same as in Example 1 to prepare the polishing pad.

[0080] The polishing pad of Comparative Example 2 had a thickness of 0.38 mm for the sealing layer and 0.95 mm for the polishing layer. The water contact angle of the support surface was 71.1°, and the bubble density of the sealing layer was 62%. The water contact angle of the polishing surface was 72.3°, and the bubble density of the polishing layer was 60%. The water vapor permeability was 300 g / m 2 -It was 24 hours.

[0081] Roughness was evaluated in the same manner as in Example 1. From Table 1, the roughness was greater than 1.0 nmRz in Comparative Example 2. This is thought to be because the water contact angle of the support surface was less than 90°, causing liquid to overflow from the pores and making it impossible to obtain high surface precision.

[0082] Comparative Example 3 A polishing pad was prepared in the same manner as in Example 5. However, the polishing pad of Comparative Example 3 was prepared by forming only a sealing layer without forming an abrasive layer.

[0083] The polishing pad of Comparative Example 3 had a sealing layer thickness of 0.94 mm. The water contact angle of the support surface was 122.0°, the bubble density of the sealing layer was 60%, and the water vapor permeability was 10.9 g / m 2 -It was 24 hours.

[0084] The roughness was evaluated in the same manner as in Example 1. From Table 1, the roughness was greater than 1.0 nmRz in Comparative Example 3. From this result, it is considered that the lack of a hydrophilic surface like the polishing surface meant that the polishing liquid could not be sufficiently retained, and therefore high surface precision could not be obtained.

[0085] [Table 1]

[0086] From the above results, it was confirmed that the polishing pad of the present disclosure is made of a resin molded body in which a polishing layer having a polishing surface with a water contact angle smaller than that of the support surface and a sealing layer having a support surface with a water contact angle of 90° or more are laminated in order, so that even if fluid pressure is applied when used for fluid-supported polishing, the fluid does not seep out to the polishing surface. In addition, since it is made of a resin molded body without an adhesive layer made of adhesive, it can maintain high conformability to the shape and warping of the workpiece. Therefore, it was found that the polishing pad of the present disclosure can sufficiently reduce the surface roughness of the workpiece compared to conventional polishing pads for fluid-supported polishing.

[0087] It should be noted that the present disclosure is not limited to the above-described embodiments, and many modifications are possible within the technical concept of the present disclosure. Furthermore, the effects described in the embodiments are merely a list of the most preferable effects resulting from the present disclosure, and the effects of the present disclosure are not limited to those described in the embodiments.

[0088] The disclosure of this embodiment includes the following configurations and methods.

[0089] (Configuration 1) A polishing pad comprising a polishing layer having a polishing surface and a sealing layer having a support surface, the polishing surface being disposed on a front surface and the support surface being disposed on a rear surface, The water contact angle of the support surface is 90° or more; a water contact angle of the polishing surface is smaller than a water contact angle of the support surface; The polishing pad is made of a resin molded body. A polishing pad characterized by:

[0090] (Configuration 2) 2. The polishing pad according to claim 1, wherein the water contact angle of the support surface is 150° or less.

[0091] (Configuration 3) 3. The polishing pad of claim 1 or 2, wherein the sealing layer contains fluororesin particles.

[0092] (Configuration 4) 4. The polishing pad according to configuration 3, wherein the content of the fluorine-based resin particles in the sealing layer is in the range of 20% by mass to 50% by mass.

[0093] (Configuration 5) 5. The polishing pad according to claim 3 or 4, wherein the fluororesin particles are polytetrafluoroethylene.

[0094] (Configuration 6) 6. The polishing pad according to any one of claims 1 to 5, wherein the polishing layer contains hydrophilic metal oxide particles.

[0095] (Configuration 7) 7. The polishing pad of claim 6, wherein the metal oxide particles are at least one of silica or alumina.

[0096] (Configuration 8) 8. The polishing pad according to claim 6 or 7, wherein the content of the metal oxide particles in the polishing layer is in the range of 20% by mass to 50% by mass.

[0097] (Configuration 9) 9. The polishing pad according to any one of configurations 1 to 8, wherein the resin molded body is a foam having bubbles, and the bubbles have a flat shape that is crushed in the thickness direction of the polishing pad.

[0098] (Configuration 10) 10. The polishing pad according to claim 9, wherein the length in the thickness direction of the flat bubbles in the polishing layer and the sealing layer is equal to or less than the thickness of the polishing layer and the sealing layer.

[0099] (Configuration 11) 11. The polishing pad according to claim 9 or 10, wherein the average bubble diameter of the bubbles on the polishing surface is in the range of 50 μm or more and 300 μm or less.

[0100] (Configuration 12) The water vapor permeability of the polishing pad is 25 g / m 2 12. The polishing pad according to any one of claims 1 to 11, wherein the polishing time is 24 hours or less.

[0101] (Configuration 13) 13. The polishing pad according to any one of claims 1 to 12, wherein the polishing pad is mainly composed of polyurethane.

[0102] (Configuration 14) 14. The polishing pad according to any one of configurations 1 to 13, wherein the thickness of the polishing pad is in the range of 0.3 mm or more and 2.0 mm or less.

[0103] (Configuration 15) An apparatus for polishing a workpiece by placing the workpiece on the polishing surface of the polishing pad according to any one of configurations 1 to 14, comprising: A base for fixing the polishing pad; a fluid reservoir for storing a fluid that applies pressure to the polishing pad from the sealing layer side.

[0104] (Method 1) A method for manufacturing an article by polishing the workpiece using the polishing apparatus according to aspect 15 to manufacture an article.

[0105] (Method 2) A method for producing a polishing pad according to any one of configurations 1 to 14, comprising the steps of: A step of placing a sealing layer precursor having a thermoplastic resin, a curing agent, and first hollow particles in a mold and then heating the sealing layer precursor to temporarily cure the sealing layer precursor; a step of placing an abrasive layer precursor having the thermoplastic resin, the curing agent, and second hollow particles on the provisionally cured sealing layer precursor in the mold, and then heating the abrasive layer precursor to provisionally cure; a step of heating the sealing layer precursor and the polishing layer precursor to fully cure them to form a sealing layer and a polishing layer; A method for manufacturing a polishing pad comprising the steps of:

[0106] (Method 3) A method for manufacturing a polishing pad according to method 2, in which, in the forming step, the sealing layer precursor and the polishing layer precursor are heated to fully harden them while compressing the inside of the mold and maintaining that state until they no longer flow, thereby forming a sealing layer, a polishing layer, and flat-shaped bubbles.

[0107] (Method 4) A method for producing a polishing pad according to any one of configurations 1 to 14, comprising the steps of: a step of placing an abrasive layer precursor having a thermoplastic resin, a curing agent, and second hollow particles in a mold and then heating the abrasive layer precursor to temporarily cure the abrasive layer precursor; a step of placing a sealing layer precursor having the thermoplastic resin, the curing agent, and first hollow particles above the provisionally cured polishing layer precursor in the mold, and then heating the sealing layer precursor to provisionally cure; a step of heating the polishing layer precursor and the sealing layer precursor to fully cure them to form a polishing layer and a sealing layer; A method for manufacturing a polishing pad comprising the steps of:

[0108] (Method 5) The method for manufacturing a polishing pad described in Method 4, in which in the forming step, the sealing layer precursor and the polishing layer precursor are heated to fully harden them while compressing the inside of the mold and maintaining that state until they no longer flow, thereby forming a sealing layer, a polishing layer, and flat-shaped bubbles. [Explanation of symbols]

[0109] 7. Resin 8. Air Bubbles 9 Fluorine-based resin particles 10 Polishing Pad 11 Polishing layer 11S polished surface 12 Middle Class 13 Sealing layer 13S Support surface 20-inch

Claims

1. A polishing pad comprising a polishing layer having a polishing surface and a sealing layer having a support surface, the polishing surface being disposed on a front surface and the support surface being disposed on a rear surface, The water contact angle of the support surface is 90° or more; a water contact angle of the polishing surface is smaller than a water contact angle of the support surface; The polishing pad is made of a resin molded body. A polishing pad characterized by:

2. 2. The polishing pad of claim 1, wherein the support surface has a water contact angle of 150° or less.

3. 2. The polishing pad of claim 1, wherein the sealing layer contains fluororesin particles.

4. 4. The polishing pad according to claim 3, wherein the content of the fluorine-based resin particles in the sealing layer is in the range of 20% by mass to 50% by mass.

5. 4. The polishing pad according to claim 3, wherein the fluororesin particles are made of polytetrafluoroethylene.

6. The polishing pad of claim 1 , wherein the polishing layer contains hydrophilic metal oxide particles.

7. 7. The polishing pad of claim 6, wherein the metal oxide particles are at least one of silica or alumina.

8. 7. The polishing pad according to claim 6, wherein the content of the metal oxide particles in the polishing layer is in the range of 20% by mass to 50% by mass.

9. 2. The polishing pad according to claim 1, wherein the resin molded body is a foam having bubbles, and the bubbles have a flat shape that is crushed in the thickness direction of the polishing pad.

10. 10. The polishing pad according to claim 9, wherein the length in the thickness direction of the flat bubbles in the polishing layer and the sealing layer is equal to or less than the thickness of the polishing layer and the sealing layer.

11. 10. The polishing pad according to claim 9, wherein the average bubble diameter of the bubbles on the polishing surface is in the range of 50 μm to 300 μm.

12. The water vapor permeability of the polishing pad is 25 g / m 2 The polishing pad according to claim 1, wherein the polishing time is 24 hours or less.

13. The polishing pad according to claim 1 , wherein the polishing pad is primarily made of polyurethane.

14. 2. The polishing pad according to claim 1, wherein the polishing pad has a thickness in the range of 0.3 mm to 2.0 mm.

15. 15. An apparatus for polishing a workpiece by placing the workpiece on the polishing surface of the polishing pad according to claim 1, comprising: A base for fixing the polishing pad; a fluid reservoir for storing a fluid that applies pressure to the polishing pad from the sealing layer side.

16. A method for manufacturing an article, comprising polishing the workpiece using the polishing apparatus according to claim 15 to manufacture the article.

17. A method for producing a polishing pad according to any one of claims 1 to 14, comprising the steps of: A step of placing a sealing layer precursor having a thermoplastic resin, a curing agent, and first hollow particles in a mold and then heating the sealing layer precursor to temporarily cure the sealing layer precursor; a step of placing an abrasive layer precursor having the thermoplastic resin, the curing agent, and second hollow particles on the provisionally cured sealing layer precursor in the mold, and then heating the abrasive layer precursor to provisionally cure; a step of heating the sealing layer precursor and the polishing layer precursor to fully cure them to form a sealing layer and a polishing layer; A method for manufacturing a polishing pad comprising the steps of:

18. 18. A method for manufacturing a polishing pad as described in claim 17, wherein in the forming step, the sealing layer precursor and the polishing layer precursor are heated to fully harden them while compressing the inside of the mold and maintaining that state until they no longer flow, thereby forming a sealing layer, a polishing layer, and flat bubbles.

19. A method for producing a polishing pad according to any one of claims 1 to 14, comprising the steps of: a step of placing an abrasive layer precursor having a thermoplastic resin, a curing agent, and second hollow particles in a mold and then heating the abrasive layer precursor to temporarily cure the abrasive layer precursor; a step of placing a sealing layer precursor having the thermoplastic resin, the curing agent, and first hollow particles on the temporarily cured polishing layer precursor in the mold and then heating the sealing layer precursor to temporarily cure; a step of heating the polishing layer precursor and the sealing layer precursor to fully cure them to form a polishing layer and a sealing layer; A method for manufacturing a polishing pad comprising the steps of:

20. 20. A method for manufacturing a polishing pad as described in claim 19, wherein in the forming step, the sealing layer precursor and the polishing layer precursor are heated to fully harden them while compressing the inside of the mold and maintaining that state until they no longer flow, thereby forming a sealing layer, a polishing layer, and flat bubbles.

Citation Information

Patent Citations

  • Abrasive pad and manufacturing method for the same

    JP2003220550A

  • Polishing tool and polishing method

    JP2004358591A